A potential therapeutic drug for osteoporosis: prospect for osteogenic LncRNAs - Meng, Fanjin; Yu, Yang; Tian, Ye; Deng, Meng; Zheng, Kaiyuan; Guo, Xiaolan; Zeng, Beilei; Li, Jingjia; Qian, Airong; Yin, Chong (Frontiers in Endocrinology, 2023)
Long non-coding RNAs (LncRNAs) play essential roles in multiple physiological processes including bone formation. Investigators have revealed that LncRNAs regulated bone formation through various signaling pathways and micro RNAs (miRNAs). However, several problems exist in current research studies on osteogenic LncRNAs, including sophisticated techniques, high cost for in vivo experiment, as well as low homology of LncRNAs between animal model and human, which hindered translational medicine research. Moreover, compared with gene editing, LncRNAs would only lead to inhibition of target genes rather than completely knocking them out. As the studies on osteogenic LncRNA gradually proceed, some of these problems have turned osteogenic LncRNA research studies into slump. This review described some new techniques and innovative ideas to address these problems. Although investigations on osteogenic LncRNAs still have obtacles to overcome, LncRNA will work as a promising therapeutic drug for osteoporosis in the near future.